Туристична анімація як інструмент соціальної коґезії в повоєнній Україні (на прикладі туристсько-рекреаційних та готельно-ресторанних закладів) - Борецька, Н.П.; Крапівіна, Г.О. (Економічний вісник Донбасу, 2025)
У статті розглянуто трансформацію туристської анімації в умовах цифровізації та повоєнного відновлення України. Визначено, що цифрові технології сприяють переходу до інтерактивної, персоналізованої та гнучкої моделі взаємодії з туристами, що потребує оновлення професійних компетентностей аніматорів та перегляду стандартів надання туристичних послуг. Окрема увага приділяється соціокультурному, економічному та символічному значенню туристської анімації у повоєнний період. Показано її роль як інструменту соціальної інтеграції, психоемоційного відновлення, популяризації національної культурної спадщини, а також розвитку мікропідприємництва та локальних громад. Наголошується на необхідності інтеграції туристської анімації в стратегії післявоєнного відновлення, регіонального розвитку та державної гуманітарної політики. The article explores the transformation of tourist animation in the context of digitalization and post-war recovery in Ukraine. It emphasizes that the integration of digital technologies leads to the emergence of an interactive, personalized, and flexible model of interaction with tourists. This transformation requires updating the professional competencies of animators, adapting educational programs, and revising service quality standards in the digital environment. Particular attention is paid to the socio-cultural, economic, and symbolic significance of tourist animation in the post-war period. Tourist animation is considered not only as a tool for recreation and entertainment but also as a mechanism for social cohesion, psycho-emotional recovery, and the revitalization of cultural potential in different regions. It contributes to the integration of internally displaced persons, veterans, children affected by traumatic events, and other vulnerable population groups by creating safe spaces for interpersonal communication and collective experience. Furthermore, animation programs aimed at promoting national cultural heritage help strengthen patriotic identity and reinforce respect for Ukrainian traditions and heroic narratives. From an economic standpoint, the development of animation services fosters micro-entrepreneurship, community activation, job creation, and diversification of regional economies, particularly in rural and post-conflict areas. Animators, as interdisciplinary professionals, play an important role in facilitating dialogue among various social groups, ethnicities, and generations. Thus, tourist animation becomes a creative tool for societal rehabilitation, the restoration of the cultural landscape, and the formation of a positive international image of Ukraine. Its systematic development should be integrated into post-war recovery strategies, regional development programs, and national humanitarian policy.